Cathepsin L promotes angiogenesis by regulating the CDP/Cux/VEGF-D pathway in human gastric cancer - Pan, Tao (Gastric Cancer, 2020)
BACKGROUND: Increasing evidence indicates that angiogenesis plays an important role in tumor progression. The function of cathepsin L (CTSL), an endosomal proteolytic enzyme, in promoting tumor metastasis is well recognized. The mechanisms by which CTSL has promoted the angiogenesis of gastric cancer (GC), however, remains unclear. METHODS: The nuclear expression levels of CTSL were assessed in GC samples. The effects of CTSL on GC angiogenesis were determined by endothelial tube formation analysis, HUVEC migration assay, and chick embryo chorioallantoic membrane (CAM) assay. The involvement of the CDP/Cux/VEGF-D pathway was analyzed by angiogenesis antibody array, Western blot, co-immunoprecipitation (Co-IP) and dual-luciferase reporter assay. RESULTS: In this study, we found that the nuclear CTSL expression level in GC was significantly higher than that in adjacent nontumor gastric tissues and was a potential important clinical prognostic factor. Loss- and gain-of-function assays indicated that CTSL promotes the tubular formation and migration of HUVEC cells in vitro. The CAM assay also showed that CTSL promotes angiogenesis of GC in vivo. Mechanistic analysis demonstrated that CTSL can proteolytically process CDP/Cux and produce the physiologically relevant p110 isoform, which stably binds to VEGF-D and promotes the transcription of VEGF-D, thus contributing to the angiogenesis of GC. CONCLUSION: The findings of the present study suggested that CTSL plays a constructive role in the regulation of angiogenesis in human GC and could be a potential therapeutic target for GC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10120-020-01080-6) contains supplementary material, which is available to authorized users.